Sleep quality and renal function among Chinese incoming college freshmen: the mediating role of lifestyle behaviors - Wang, Huiying; Li, Jiali; Han, Yaohui; Zhai, Shilei; Liu, Yumeng; Shen, Peipu; Shen, Guifang; Xiao, Lishun (Frontiers in Public Health, 2025)
ObjectiveThis study investigates the association between sleep quality and renal function indicators, with a focus on how lifestyle behaviors mediate this relationship among Chinese incoming college freshmen during post-examination vacation period.MethodsThis cross-sectional study included 3,743 non-smoking, non-drinking freshmen from two universities in Xuzhou, China. Data on demographics, sleep quality, and blood biochemical indicators were collected through self-administered questionnaires, Pittsburgh Sleep Quality Index (PSQI) and physical examinations. Multiple logistic regression (MLR) was applied to explore the related biochemical indicators associated with sleep quality. Structural equation modeling (SEM) was subsequently used to evaluate the mediating effects of lifestyle factors in this relationship.ResultsHigher creatinine levels (OR = 1.01, p = 0.002) increased the risk of poor sleep quality, while higher urea levels (OR = 0.87, p < 0.001) decreased it. Unhealthy lifestyle behaviors were also associated with sleep quality, including habitual caffeinated beverage intake (OR = 1.11, p = 0.003) and daily screen time (OR = 1.08, p = 0.001). Stratified analyses by gender further supported these associations, especially in females. SEM revealed that sleep quality could affect renal function (represented by creatinine and urea) though the independent mediating effect of daily screen time and the chain mediating effect of caffeinated beverage intake and daily screen time.ConclusionThese findings suggest that promoting healthy sleep, limiting screen exposure, and reducing caffeine consumption may help protect renal health in incoming college freshmen.